Local trends in Gastrointestinal diseases: Audit review of Endoscopy data at Sir Ganga Ram Hospital (Journal of Fatima Jinnah Medical University, 2018)
Objective: To review endoscopic data to assess local trends of gastrointestinal diseases and its complications, in order to improve our quality of service.Design: Retrospective review of comparative data for two years i.e 2009/10.Data sources: Data collected from record keeping registers as well from special booking performas.Review methods :Data was formulated into tables according to patients demography, initial clinical & biochemical presentation , nature of procedure and outcome.Results: Record of 420 procedures were reviewed from 2009/10. More than 80% were related to upper GI tract. Most of the procedures were diagnostic with 20% had therapeutic intervention in form of Variceal banding. Majority 60% presented with features of upper GI bleeding mostly due to oesophageal varices, keeping in line with high prevalence of Chronic Hepatitis C infection and cirrhosis.Conclusion: This was a review of our Endoscopy service over the period of two years. It has suggested a high prevalence of liver diseases and our satisfactory ability to deal with its serious complications like Variceal Haemorrhage. We have also highlighted our deficiency areas and put forward suggestions to improve our efficiency.
Keywords: GI(Gastrointestinal system), HPB(Hepatobiliary system), Oesophageal Varices- dilated veins, Gastritis-Inflammation of Stomach wall, Oesophagitis(Inflammation of oesophagus), Ulcerative Colitis(Inflammation of colonic wall)